Frequency of dyspnea related to intake of ticagrelor or clopidogrel in patients with chronic coronary syndrome undergoing coronary intervention - Dunya Habeeb Shnain; Ghassan Mohammed Mahmood; Sara Omar Ahmed (Кардиоваскулярная терапия и профилактика, 2024)
In patients with chronic coronary syndrome, ticagrelor decreases cardiovascular events more efficiently than clopidogrel. In several studies investigating novel P2Y12 inhibitors dyspnea has been detected. A rise of adenosine blood levels is supposed to be one of cases of dyspnea induced by ticagrelor. Dyspnea is a prevalent and complex symptom. It is associated with deterioration of the quality of life and hospital readmission.Aim. To determine the frequency of dyspnea related with ticagrelor or clopidogrel intake in patients with stable coronary artery disease undergoing coronary intervention. Also, to determine which patients could continue ticagrelor intake and which patients couldn’t, and show the causes of ticagrelor discontinuation.Material and methods. Between October 2023 and January 2024, an observational prospective comparative case-control study was conducted at Baghdad Heart Center in Baghdad Teaching Hospital in Medical City. In this study, individuals with stable coronary artery disease who just had therapeutic catheterization and dual antiplatelet therapy were included. The patients from group 1 received aspirin and ticagrelor, while those from group 2 received aspirin and clopidogrel.Results. A total of 120 patients were included. With the ticagrelor intake, the severity of dyspnea was classified as mild 64.2% (77 [120]) and moderate 19.1% (23 [120]). About 16.7% (20 [120]) had no dyspnea at all. The difference between patients who continued ticagrelor intake (16%) and those who stopped using it (84%) was significant. With clopidogrel intake no dyspnea was recorded.Conclusions. According to our findings, the risk or occurrence of dyspnea is only evident in patients who received ticagrelor. When compared to irreversible P2Y12 inhibitors like clopidogrel, the reversible P2Y12 antagonist ticagrelor has a higher incidence of dyspnea in increasing order.